Factors Influencing the Choice Decisions of Students at the Oudomxay Integrated Vocational Educational and Training College - phoumiphonh, sayyasith (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Factors Influencing the Choice Decisions of Students at the Oudomxay Integrated Vocational Educational and Training College is a survey study using questionnaires as a tool to collect data from the sample group to analyze Factors Influencing the Choice Decisions to Apply. The results of the study found: Analyze the importance of the factors influencing the choice decisions of students at the Oudomxay Integrated Vocational Educational and Training College. There are 242 respondents to the questionnaire. The average value of all factors is 3.67 (SD: 1.22). Compared to the criteria for determining the average score, it is found to be very important, followed by the curriculum factor with an average value equal to 3.79 (SD: 1,017). Compared to the criteria for determining the average score, it is found to be very important, and the lowest average value is family factors with an average value equal to 3.41 (SD: 1,158). Compared to the criteria for determining the average score, it is found to be very important. Factors that make students decide to apply to Oudomxay Vocational Educational and Training College include: age, the courses offered are in demand in the labor market, there are activities for the knowledge development of students, teachers are reputable and have teacher ethics, registration fees, service charges, and tuition fees are not high, and society appreciates the knowledge and skills of the students who study there. These variables affect the probability that students will choose to apply to Oudomxay Vocational Educational and Training College over other institutions with different levels of statistical significance.